Pengaruh Penerapan Program Psikoterapi Kognitif Perilaku Terhadap Penurunan Gejala Depresi pada Remaja - Olivia Eka Heryanto Putri; Ahmad Rizal Firmansyah; Mohammad Sulistyo Muharram Wibisana; Aurelia Bella Belqhiska; Denny Oktavina Radianto (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study outlines the problem of depression in adolescents as one of the major issues in public health, with far-reaching implications for their quality of life and well-being. The prevalence rate of depression increases during adolescence, with serious repercussions such as suicide risk, behavioral disorders, substance abuse, and academic and social problems. Cognitive Behavioral Psychotherapy (CBT) has been shown to be effective in treating adolescent depression by modifying maladaptive thought and behavior patterns. Group-based CBT therapy has also been shown to be beneficial in reducing depressive symptoms and preventing further development of subclinical depression. However, there are still challenges that need to be addressed, such as the low number of adolescents seeking or receiving mental care, the stigma associated with mental health problems, and the gap between scientific research and clinical practice. Increasing awareness of the importance of mental care, reducing stigma, and better integration between research and clinical practice can improve access and effectiveness of treatment. Therefore, the use of group-based CBT therapy in the treatment of adolescent depression has the potential to be an important step in improving adolescents' mental health and overall quality of life.